Unlocking early academic skills: children’s cognitive processes, learning skills, and parental beliefs and behaviors predicting children’s language and math skills - Meesak, Anne-Mai; Rozgonjuk, Dmitri; Õun, Tiia; Kikas, Eve (Frontiers in Psychology, 2025)
IntroductionThis study explored the emerging academic skills of five-year-old Estonian children, focusing on cognitive processes, learning skills, and parental beliefs and behaviors. While previous research has concentrated on a limited number of skill areas and aspects of the home environment, this study aimed to provide a more comprehensive understanding of children’s early learning by studying multiple skills and parental characteristics concurrently.MethodsData was collected through direct e-assessments of children’s skills alongside parental questionnaires (N = 279).ResultsWe found positive relationships between children’s cognitive processes, language, math, and learning skills, emphasizing the importance of considering multiple skills together. While children’s cognitive processes and learning skills contribute to the development of their academic skills, parental beliefs and behaviors are also important. Considered as a whole, parental perceptions of their children’s cognitive difficulties and kindergarten involvement predicted both language and math skills, whereas parents’ education and social expectations were only related to language outcomes. In contrast, children’s learning skills predicted solely their math skills. Importantly, the frequency of parental home activities was not directly linked to children’s academic skills, showing that their relationship in early childhood might be more complex.DiscussionThese results highlight the significance of a holistic approach to children’s development, integrating both child- and parent-related factors and suggesting that active participation in kindergarten and fostering social skills may outweigh high academic expectations and frequency of home-based activities in supporting children’s academic growth.